Design Of Quasi-Lumped Element Bandpass Filter - Cho, Sheau Fen (Universiti Sains Malaysia, 2006)
This dissertation demonstrates the design of quasi-lumped element bandpass filters operating at 2 GHz. The design was simulated before being implemented, because it was easy to make a mistake in the calculations and waste a lot of time. Agilent Advance Design System software (ADS) a computer-aided design CAD tool is used for the simulation purpose. In implementation, substrate Duroid is selected. The first part of this dissertation, the quasi-lumped element resonator consisting of the interdigital capacitor parallel with a straight line or meander line inductor is designed. The frequency response of the resonator depends on the length, width, number of interdigital fingers and gap is used in the quasi-lumped element resonator design. The advantage of using microstrip quasi-lumped element resonator is low loss because it reduces the connection between devices and PCB. Beside that, this resonator design is more low-cost, compact and simple to realize by comparing to the other resonators structure. The second part of this dissertation, a quasi-lumped element bandpass filter is built using three quasi-lumped element resonators. The final design is fabricated on Duroid-type printed circuit board after simulation. Measurement will be carried out using the vector network analyzer (VNA) after the fabrication. The network analyzer instrument is used to measure the scattering parameters (magnitude and phase) of two-port microwave network. The simulation and measurement result will be discussed in this dissertation. A meander line inductor achieves further filter miniaturization. Low-insertion loss, high return loss and high Q factor are simultaneously required for filters. In addition, these filters should be compact, low-cost, and high performance. This project includes literature review, simulation, fabrication and measurement.